Report From The 5th Doctoral Conference Young scientists at the University. The areas of research and academic passions on the 6th December in Poznan - Adamczewski, Jakub (Biuletyn Historii Wychowania, 2020)
Report From The 5th Doctoral Conference Young scientists at the University. The areas of research and academic passions on the 6th December in Poznan